The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.7759/cureus.528
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fluids in Sepsis

Abstract: Sepsis is a systemic inflammatory response to severe infection causing significant morbidity and mortality that costs the health care system $20.3 billion annually within the United States. It is well established that fluid resuscitation is a central component of sepsis management; however, to date there is no consensus as to the ideal composition of fluid used for resuscitation. In this review, we discuss the progression of clinical research comparing various fluids, as well as the historical background behin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…62 We refer the reader to excellent reviews regarding optimal fluid therapeutic strategies in sepsis. 62–64…”
Section: Sepsis Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…62 We refer the reader to excellent reviews regarding optimal fluid therapeutic strategies in sepsis. 62–64…”
Section: Sepsis Pathophysiologymentioning
confidence: 99%
“…[59][60][61] In addition to the findings from this study, the restricted accessibility, safety issues, and the expensive value of colloids shifted the debate toward identifying the ideal crystalloid composition (eg, Ringer lactate, Ringer acetate, etc). 62 We refer the reader to excellent reviews regarding optimal fluid therapeutic strategies in sepsis. [62][63][64] The utilization of magnetic resonance imaging (MRI) in the diagnosis of SAE offers a unique opportunity in capturing some of the morphologic, ischemic, and metabolic alterations associated with sepsis.…”
Section: The Cns In Sepsis: Sickness Behavior and Saementioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis is one of the main reasons for ICU admissions, and 6%-30% of all ICU patients are assumed to suffer from sepsis [ 44 ]. The disease is associated with a high mortality and a considerable cost burden [ 45 - 47 ]. The adequate initial volume application is essential in the initial resuscitation of sepsis [ 8 - 11 ], and it affects patients’ outcome and mortality risk [ 4 - 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initial fluid resuscitation with crystalloids should be started to achieve minimum of 30 mL kg −1 of fluids in the first 3 h in patients with sepsis-induced tissue hypoperfusion. 35 , 47 , 48 Despite lack of controlled data to support this volume and rate of fluid delivery, some interventional studies have described this as usual practice during initial resuscitation, and observed evidence supports this practice. 46 , 49 …”
Section: Care Bundlesmentioning
confidence: 99%